KORELASI KEMANDIRIAN DAN KEDISIPLINAN BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA PADA MASA PANDEMI (COVID-19) - Rianita Simamora (MES: Journal of Mathematics Education and Science, 2021)
Every student has different intelligence to be able to learn a basic mathematical concept. However, learning mathematics is not just doing calculations using formulas or using logic to conclude. However, other factors needed to achieve mathematics learning achievement, especially in online-based learning during the pandemic (COVID-19). Other factors that influence mathematics learning achievement include independence and discipline in learning mathematics online. This research is a descriptive correlational study using a survey. This research was conducted on class VII students of SMP Negeri 5 Pematangsiantar, amounting to 56 people. The instrument used was a questionnaire and documentation which was analyzed using the correlation test. The results showed that there was a correlational relationship between the three variables, where there was a correlation between learning independence and learning achievement, learning discipline with learning achievement, and learning independence with learning discipline.